Digital Public Diplomacy of the Ministry of Foreign Affairs through the Instagram Account @KEMLU_RI Indonesia's G20 Presidency in 2022 - Hikmawan, Rizky; Fathun, Laode Muhammad; Astuti, Wiwiek Rukmi Dwi (Intermestic: Journal of International Studies; Vol 9 No 1 (2024), 2025)
This paper aims to evaluate the implementation of the Ministry of Foreign Affairs' digital public diplomacy through social media, Instagram. Given the many uploads that have been made by the @kemlu_ri account, this research will focus on the content of Indonesia's presidency of the G20 in 2022. The G20 presidency was chosen given its status as a national agenda that has international attention, both from the institutional aspect and the post-pandemic situation. The theories/concepts used in this research are digital public diplomacy and social media. The method used is qualitative by making @kemlu_ri content uploads as a primary data source plus interviews with the Directorate of Information and Media, Ministry of Foreign Affairs, as a form of data verification. From the evaluation conducted, the author argues that the use of social media Instagram as a means of digital public diplomacy related to Indonesia's presidency in the G20 in 2022 is not optimal. The argumentation given in this paper refers to the three dimensions of social media in digital public diplomacy, namely: (i) agenda-setting; (ii) presence expansion; and (iii) conversation-generating.